2020
DOI: 10.1109/jsen.2019.2948681
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Sensitivity Limitations of Nanomechanical Resonant Sensors Due to Thermomechanical Noise

Abstract: Nanomechanical resonators are used as high performance sensors of physical stimuli such as force and mass changes. Any such physical stimulus produces a shift in the resonance frequency of the nanomechanical structure, which can be measured accurately by using a feedback system that locks the frequency of a signal generator to the resonance. Closed-loop frequency tracking is the most prevalent technique in the fields of nanomechanical sensors and non-contact atomic force microscopy. Ultimate performance of sen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 40 publications
9
59
0
Order By: Relevance
“…Finally, closed-loop measurements are performed, where it can be shown that τ r can be increased through variation of the loop bandwidth. All Allan deviation measurements are corroborated by computations based on a theoretical model [26] and good agreement is observed both for open loop and closed loop.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Finally, closed-loop measurements are performed, where it can be shown that τ r can be increased through variation of the loop bandwidth. All Allan deviation measurements are corroborated by computations based on a theoretical model [26] and good agreement is observed both for open loop and closed loop.…”
Section: Introductionsupporting
confidence: 55%
“…This was attributed to a flattening of the phase noise spectrum at low frequencies. A thorough theoretical investigation of the same scenario by Demir et al however found no Q dependence of the frequency stability [26].…”
Section: Introductionmentioning
confidence: 88%
“…Four imprecision sources affecting the system are modelled through different inputs: signal source noise V src (s), thermomechanical noise F thm (s), resonance frequency fluctuations Ω n (s) and detector noise V msr (s), whose descriptions can be found in Appendix II. To simplify the analysis, all the signals are considered approximately harmonic, and the system is linearized around its operating point ω a = ω n [21], [24]. This results in the phase-space system shown in Fig.…”
Section: Fundamentalsmentioning
confidence: 99%
“…a closed-loop scheme) is needed to continually adjust the driving frequency, such that it stays near the resonance frequency. Two types of closed-loop schemes for driving resonant sensors can be found in the literature: direct feedback oscillators [18], [19], and phase-locked loops (PLL) [20], [21]. The former need automatic gain controllers to avoid non-linear behaviour at large amplitudes that would be detrimental for the frequency precision, or even more sophisticated controllers to operate the resonator at optimal points of the non-linear regime [22], [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation